The Effect of Benson Relaxation on Anxiety Levels for Third Trimester Pregnant Women: A Pilot Study - Nastiti, Aria Aulia; Yunitasari, Esti; Tyas, Dhini Kartika Ning (International Journal of Psychosocial Rehabilitation, 2020)
Anxiety in third-trimester pregnant women is increasing and can cause premature birth, preeclampsia, and disorders during labor. The purpose of this study was to determine the ef ects of Benson’s relaxation on anxiety during pregnancy in the third trimester. This study was quasi-experimental with 20 pregnant women referred to health center services randomized into two groups: control and tests. They were then asked to do relaxation for 15-20 minutes for one month twice a day. The anxiety levels were compared using the Prenatal Anxiety Screening Scale (PASS) and the obtained result was analyzed using the Wilcoxon and Mann-Whitney test at a significance level <0.05. Based on the obtained result, 80 % of mothers were aged from 20-35 years old. The mean and standard deviation of anxiety level in the intervention group before Benson relaxation was 32.3±5.36 and after relaxation was 25.5±2.8. Analysis (Mann-Whitney test) of anxiety level before and after intervention in the test group showed a significant dif erence P=0.04. Analysis (Wilcoxon) of anxiety level in the intervention group and the control group showed a dif erence (P= 0.008; P=0.083). This demonstrated the positive ef ect of Benson’s relaxation on decreased anxiety level in pregnancy. Education is recommended for all pregnant women in the third trimester of pregnancy in health centers.